Older couples' labour market reactions to family disruptions - David Haardt (University of Essex, Institute for Social and Economic Research (ISER), 2007)
In this paper, I analyse how spouses in older couples react to shocks or surprises in their partners labour income using data from the British Household Panel Survey, 1991-2004. Wives labour supply proves to be much more sensitive to shocks than husbands. After a divorce or separation, wives reduce their labour supply while the effect on husbands labour supply is positive or not statistically significant. If a wife becomes unemployed, it does not affect her husbands labour supply while wives whose husband becomes unemployed reduce their labour supply, too. A decline in husbands health causes the wife to reduce her working hours while husbands tend to increase their labour supply when facing a decline in wifes health. Partners death does not have statistically significant labour supply effects. Negative income shocks due to other reasons (such as choice) tend to reduce partners labour supply and vice versa, but only slightly.
Keywords: 330